The worlds of harpsichord and organ liber amicorum David Fuller - Gustafson, Bruce 1945- (Pendragon Press, 2019)
After a Foreword by William Christie reflecting on a half-century of musical friendship with David Fuller, essays by an international roster of musicologists present new research about the music, theory, and organology of the harpsichord and the organ. Chronologically, the subjects range from the seventeenth to twentieth centuries, all the articles being written by colleagues and former students of the honoree. A closing section presents a survey of the career and writings of David Fuller with tributes from distinguished colleagues.
Includes index
Keywords: Geschichte; Harpsichord -- History; Organ -- History; Festschrift